Clinical legal education : benefitting from the Banaras experience - Ansari, Abdul Haseeb (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
While imparting technical and medical education, institutions teach also practical knowledge to their students. When they are in final year, they have to pursue a project paper based on laboratory-based research. In the same year, engineering students, information technology students, and other students pursuing other technical education have to go for industrial training. Similarly, medical students have to complete at least one year as a junior doctors at hospitals. There was no such practical exposure to law students. It is for this reason that a number of institutions of higher learning around the world started clinical legal education; and some of them, made it a part of their curriculum. In India, Banaras Law School, along with few other such institutions, took the lead in clinical legal education. The paper discusses the Banaras model and offers certain suggestions so that it could be followed by other institutions.